Perceptions and expectations of pregnant women about the type of birth - Roberta Marielle Arik; Cristina Maria Garcia de Lima Parada; Vera Lúcia Pamplona Tonete; Fernanda Cristina Manzini Sleutjes (Associação Brasileira de Enfermagem, 2019)
ABSTRACT Objective: to understand the perceptions and expectations of pregnant women about the type of birth. Method: this is a qualitative research, based on the assumptions of the Humanization of Obstetric Care. 15 pregnant women were interviewed twice at the beginning and the end of gestation between October 2015 and May 2016. Data were analyzed according to the method of the Discourse of the Collective Subject. Results: the discourses were associated with four themes: Advantages of vaginal birth over cesarean section; Fear and unpredictability of vaginal birth; Importance of the doctor in the definition of the type of birth; and Influence of family and friends in choosing the type of birth. Final considerations: according to pregnant women, vaginal birth has more benefit compared to cesarean section. However, during gestation and birth, fear of pain and the unexpected, and medical opinions of friends and family against vaginal birth strongly influence the choice of cesarean section.